A retrospective study of clinical profile and outcome of patients with rodenticide poisoning in tertiary care teaching hospital, Mandya Karnataka, India - S., Rajashekar; M., Prakash G. (International Journal of Advances in Medicine, 2020)
Background: Poisoning is the major health problem in developing countries like India. Rodenticides are one of the commonest substances used for poisoning in India. Rodenticides are the substances used to kill rats. They differs from chemical composition and toxicity profile. Prognosis mainly depends on chemical content of poison.Methods: This retrospective record-based study was conducted between October 2018 to September 2019 at MIMS tertiary care teaching hospital, Mandya, Karnataka, India. Data regarding age, sex, marital status, occupation, socioeconomic status, type of poison, route of exposure, clinical presentation, complications and outcome of poisoning and associated comorbid conditions were collected from the hospital records and documented in the pre-structured proforma. Descriptive analysis was carried out by the mean and standard deviation for quantitative variables, frequency and proportion for categorical variables.Results: Out of 126 study subjects, 77 (61.11%) were female, 49 (38.89%) were male. Most common age group was 21 to 30 years (45.23%), followed by 31 to 40 years (26.19%) group. Most common poison was zinc phosphide (52.39%), followed by yellow phosphorous (30.16%). Mode of poisoning was suicidal (94.4%) followed by accidental (5.6%).Most common symptom at presentation was nausea, vomiting (62.6%) followed by pain abdomen (52.4%).Most common complication was hepatitis 34 (26.98%) patients, followed by hepatic encephalopathy in 6 (4.76%) and cardiogenic shock in 6 (4.76%) patients. Total mortality was 8 (6.3%).Conclusions: Among rodenticides zinc phosphide was most common consumed poison in present study. Yellow phosphorous was most toxic poison and Aluminium phosphide was most lethal poison. Even though there is no specific antidote, early symptomatic treatment is the key in reducing the mortality.